2017
DOI: 10.18632/oncotarget.17868
|View full text |Cite
|
Sign up to set email alerts
|

Enolase 1 stimulates glycolysis to promote chemoresistance in gastric cancer

Abstract: Chemotherapy is the major choice for the cancer treatment of early and advanced stages. However, intrinsic or acquired drug resistance significantly restricts the clinical efficacy of chemotherapy. It is critical to develop novel approaches to detect and overcome drug resistance. In this study, we demonstrated that accelerated glycolysis played a pivotal role in both intrinsic and acquired cisplatin-resistance of gastric cancer cells. The metabolic reprogramming of cisplatin-resistant cells was characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 63 publications
9
88
0
1
Order By: Relevance
“…17,[19][20][21][22]25,26 The present research described above also confirmed that ENO1 is highly expressed in chemoresistant SCLC cells. 17,[19][20][21][22]25,26 The present research described above also confirmed that ENO1 is highly expressed in chemoresistant SCLC cells.…”
Section: Fgfrl1 Promotes Chemoresistance Of Sclc Through Eno1supporting
confidence: 86%
See 1 more Smart Citation
“…17,[19][20][21][22]25,26 The present research described above also confirmed that ENO1 is highly expressed in chemoresistant SCLC cells. 17,[19][20][21][22]25,26 The present research described above also confirmed that ENO1 is highly expressed in chemoresistant SCLC cells.…”
Section: Fgfrl1 Promotes Chemoresistance Of Sclc Through Eno1supporting
confidence: 86%
“…Increasing evidence has shown that ENO1 can function as an oncogenic protein by promoting cell proliferation, invasion and metastasis in many cancers. 17,[19][20][21][22]25,26 The present research described above also confirmed that ENO1 is highly expressed in chemoresistant SCLC cells. To examine whether ENO1 promotes chemoresistance of SCLC, we knocked down its expression in chemoresistant SCLC cells and then analysed drug resistance.…”
Section: Fgfrl1 Promotes Chemoresistance Of Sclc Through Eno1supporting
confidence: 86%
“…Previous studies have dealt with changes in energy metabolism that are coupled to CDDP resistance. Thus, it has been reported for different CDDP-resistant cell lines that they increase glycolysis (Qian et al, 2017), switch to oxidative phosphorylation (Galluzzi et al, 2014;Matassa et al, 2016;Wangpaichitr et al, 2017), and/or increase GLN metabolism by upregulating the GLN transporter ASCT2 and GLS (Hudson et al, 2016;Wangpaichitr et al, 2017). According to one study, the critical target explaining glutamine metabolism-linked CDDP resistance was GLS, meaning that knocking down GLS was sufficient to re-sensitize CDDP-resistant ovarian cancers to CDDP, while its transgenic overexpression in CDDPsensitive cells could confer CDDP resistance (Hudson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, and consistent with the function of the intestine, we find a number of enzymes involved with glucose metabolism, such as enol-1 an enolase, ipgm-1 a phosphoglycerate mutase, and 3 out of 4 glyceraldehyde-3-phosphate dehydrogenases ( gpd-1 , gpd-2 and gpd-4 ). The human orthologue of the C. elegans gene enol-1 , eno1 has been previously identified as a target of miR-22 in the context of human gastric cancer (Qian et al 2017). In addition, some of our top hits are the fatty acid desaturase enzymes fat-1 , fat-2 , fat-4 and fat-6 , which are all involved with fatty acid metabolism, suggesting that these metabolic pathways are subjected to a high degree of regulation in the intestine.…”
Section: Resultsmentioning
confidence: 99%